Can the laboratory affect the investigation and diagnosis of primary biliary cirrhosis?. Issue 4 (3rd February 2006) - Sinclair, D; Spedding, A; Young, R
Abstract : Background: Primary biliary cirrhosis (PBC) is an autoimmune liver disease characterised by the presence of various laboratory abnormalities but the precise role of laboratory staff in initiating clinical referral and subsequent biopsy is not clear. Objective: To examine the impact of laboratory abnormalities in the investigation of PBC. Methods: In a retrospective study of laboratory results over nine years from 1996, computer records were reviewed to identify how many referrals for biopsy were initiated and subsequent diagnoses made as a result of clinical signs, raised serum alkaline phosphatase activity (ALP), raised IgM concentration, or positive mitochondrial antibodies accompanied by a clinical comment from the laboratory suggesting further action. Results: 22 diagnoses of PBC were confirmed by histopathology. Eleven had high ALP activity which had follow up tests initiated by the laboratory (mitochondrial antibodies or IgM or both) and a comment added suggesting further investigation into the possibility of PBC. Seven had abnormal liver antibodies and one had a high polyclonal IgM concentration which prompted the relevant follow on testing and comments. One had an earlier diagnosis made on serological/clinical grounds and the biopsy was a confirmatory measure. One had no liver related antibodies. One had a request by laboratory staff for follow on tests but these were not asked for in subsequent samples by the requesting clinician. Conclusions: There is a positive role for laboratory staff in the diagnosis of PBC. Unexplained rises in ALP activity, positive mitochondrial antibodies, or raised IgM concentrations should be investigated more fully by laboratory staff and advice given to prompt a clinical referral for review and biopsy.